Space exploration as a catalyst for medical innovations - Scarpa, Julia; Parazynski, Scott; Strangman, Gary (Frontiers in Medicine, 2023)
Aerospace research has a long history of developing technologies with industry-changing applications and recent history is no exception. The expansion of commercial spaceflight and the upcoming exploration-class missions to the Moon and Mars are expected to accelerate this process even more. The resulting portable, wearable, contactless, and regenerable medical technologies are not only the future of healthcare in deep space but also the future of healthcare here on Earth. These multi-dimensional and integrative technologies are non-invasive, easily-deployable, low-footprint devices that have the ability to facilitate rapid detection, diagnosis, monitoring, and treatment of a variety of conditions, and to provide decision-making and performance support. Therefore, they are primed for applications in low-resource and remote environments, facilitating the extension of quality care delivery to all patients in all communities and empowering non-specialists to intervene early and safely in order to optimize patient-centered outcomes. Additionally, these technologies have the potential to advance care delivery in tertiary care centers by improving transitions of care, providing holistic patient data, and supporting clinician wellness and performance. The requirements of space exploration have created a number of paradigm-altering medical technologies that are primed to revitalize and elevate our standard of care here on Earth.